Mengembangkan Potensi Peserta Didik Dalam Pembelajaran PAI Berbasis TIK pada Abad ke 21 (opsi judul: Potensi Peserta Didik Abad 21 pada Pembelajaran Fikih dan SKI MA Darul Huda Mayak - Umi Isroqatul Munawaroh (https://ejournal.insuriponorogo.ac.id/, 2026)
This research was conducted with the aim of seeing how the media is used in learning, student activity, and the potential that develops after learning by utilizing ICT-based media. The type of research carried out was qualitative research using data collection techniques in the form of observations and interviews with Fiqh and SKI subject teachers. The research location is at Madrasah Aliyah Darul Huda which is in Mayak Village, Tonatan District, Ponorogo Regency. Precisely in the learning of Fiqh class 11 IIA J, SKI class 10 General P, and Fiqh class 10 General W. From the research conducted, it was found that learning using ICT media can generate student interest during the learning process. During the learning process, students tend to be active in the process of asking, answering and providing feedback.